Knowledge, attitude, and practice towards national health programs among MBBS students in a tertiary care centre of north India: a cross-sectional study - Gupta, Monika; Nim, Dwividendra Kumar; Shukla, Jitendra; Chaurasia, Rakesh Chandra (International Journal of Basic & Clinical Pharmacology, 2025)
Background: National health programmes (NHPs) are pivotal to India’s public health strategy, and medical graduates are expected to understand and implement them effectively. However, undergraduate training may not uniformly equip students with the necessary competencies. This study aimed to assess the knowledge, attitude, and practice (KAP) regarding NHPs among MBBS students at different academic levels. Methods: A cross-sectional, questionnaire-based study was conducted among 489 MBBS students (3rd year, final year, and interns) in three months from March 2025 to May 2025 at a tertiary care medical college in north India. A self-designed, structured and validated KAP questionnaire covering 10 knowledge items, 10 attitude statements, and 10 practice-related questions was administered. Descriptive statistics for comparative analysis, and results were visualised through line graphs and box plots. Results: Knowledge and practice scores improved with academic progression, with final-year students scoring the highest (mean knowledge score: 4.82±1.75; practice: 6.73±2.47). Attitude scores remained uniformly positive across all groups (mean range: 1.99-2.09). Third-year students had the lowest knowledge and practice scores. Analyses revealed the presence of low outliers in all three domains, more prominent in junior batches. Overall, awareness of programs like Ayushman Bharat, NTEP, and eSanjeevani was relatively high, while misconceptions remained regarding schemes like PM-JAY and ABDM. Conclusions: While attitudes toward NHPs were consistently favourable, knowledge and practice varied by academic year. The study underscored the need to integrate program-based learning and community engagement activities earlier in the undergraduate curriculum to strengthen public health readiness among future doctors.